(untitled) (Research, Society and Development, 2021)
The article aims to identify the perceptions of student motivation during the COVID-19 pandemic period. Motivation involves biological, emotional and social factors. It can be said that it is an impulse that makes people chase their goals, being very important in fulfilling their tasks. Without motivation, human beings feel apathetic to accomplishing and achieving their personal and/or professional goals. It can occur through an energy, inner force, which can be called intrinsic motivation or self-motivation. With the pandemic period, due to the suspension of classroom classes and limited resources, we applied the following qualitative research with some public school students in the State of Rio de Janeiro, specifically in the city of Carapebus. What is Motivation? Are you motivated to study in time of Pandemic, justify your answer? What are the biggest difficulties encountered? Suggestions of activities you would like to do during this period?